Trust, transparency and transnational lessons from COVID-19 - Alistair Cole; Julien S. Baker; Dionysios Stivas (Journal of Risk and Financial Management, 2021)
The article engages in an exercise in reflexivity around trust and the COVID-19 pandemic. Common understandings of trust are mapped out across disciplinary boundaries and discussed in the cognitive fields in the medical and social sciences. While contexts matter in terms of the understandings and uses made of concepts such as trust and transparency, comparison across academic disciplines and experiences drawn from country experiences allows general propositions to be formulated for further exploration. International health crises require efforts to rebuild trust, understood in a multidisciplinary sense as a relationship based on trusteeship, in the sense of mutual obligations in a global commons, where trust is a key public good. The most effective responses in a pandemic are joined up ones, where individuals (responsible for following guidelines) trust intermediaries (health professionals) and are receptive to messages (nudges) from the relevant governmental authorities. Hence, the distinction between hard medical and soft social science blurs when patients and citizens are required to be active participants in combatting the virus. Building on the diagnosis of a crisis of trust (in the field of health security and across multiple layers of governance), the article renews with calls to restore trust by enhancing transparency.
Keywords: 330; COVID-19; coronavirus disease; trust; transparency; political trust; social trust; transnational; transdisciplinary